Using novels in the language classroom at Hebron University / Rasha Nabeel Siaj and Mohammed A A Farrah - Siaj, Rasha Nabeel; Mohammed A, A Farrah (Universiti Teknologi MARA Cawangan Kedah, 2018)
This quantitative and qualitative paper investigated the use of novels in the EFL classroom. It examined students’ attitudes towards using novels in the EFL classroom; evaluated the advantages of using novels and whether they motivate students, develop their linguistic level, and enrich their cultural knowledge. Moreover, it identified certain problems that students may face in the process of learning novels in the EFL classroom. A total of 56 students participated in this study and responded to the questionnaire in the fall semester of 2015/2016 at Hebron University, Palestine. In addition, the researchers interviewed three instructors teaching at the English department. The findings of the questionnaire showed that students held positive attitudes towards using novels in the EFL classes. Mainly, they agree that novels have a number of advantages. For example, novels can motivate them, enrich their cultural knowledge, and improve their language ability. The interview with instructors revealed advantages of using novels and some challenge. Finally, researchers recommend that teachers keep using literature in the language classrooms and students keep reading novels due to their benefits